Three newly described species of Carex sect. Fecundae (Cyperaceae) from Central America and typification of two related names - Lois, Raúl; Acedo, Carmen; Reznicek, Anton A.; Jiménez-Mejías, Pedro (Phytotaxa, 2023)
Three new species of Carex sect. Fecundae (Cyperaceae) are described from Central America. Carex orothanatica from Costa Rica, Carex siguanabae occurring in El Salvador and Honduras, and Carex via-aquae from Costa Rica and Panama. The three new species are compared with relatives. In addition, two related names, Carex lehmanniana Boott, and C. lehmaniana var. simplex Kük., are lectotypified.